'It all dials back to safety': A qualitative study of social and economic vulnerabilities among transgender women participating in HIV research in the USA. Issue 1 (19th January 2020) - Reisner, Sari L; Chaudhry, Aeysha; Cooney, Erin; Garrison-Desany, Henri; Juarez-Chavez, Elisa; Wirtz, Andrea L
Abstract : Objectives: Transgender women (TW) are highly burdened by HIV infection in the USA. Research is needed into drivers of the HIV epidemic for TW, including longitudinal studies to identify risks for incident HIV infection and optimal intervention targets. This formative research sought to understand TW's experiences with, perceptions of and barriers and facilitators to HIV research participation to inform future research implementation. Design: Between August 2017 and January 2018, five online synchronous computer-mediated focus groups were conducted in English and two in Spanish. Recruitment used a mixed format of technology, such as geotargeted social media, and non-technology infused methods, such as peer referrals. Maximum variation sampling was used to enrol participants across a wide range of characteristics. Qualitative codes were iteratively developed and applied to focus group discussion transcripts by independent analysts. Setting: Participants were recruited from Atlanta, Baltimore, Boston, Miami, New York City and Washington D.C. Participants: Participants identified as TW≥18 years and resided in one of the six metropolitan areas or outlying regions. 33 participants elected to partake in English focus groups and eight participated in Spanish-led groups. Results: The geographically diverse sample had a mean age of 41.1 years (SD=13.6), and 34% identified as Black African American and 29% as Hispanic/Latina. Social and economic factors were found to shape HIV research participation for TW. Barriers to HIV research participation included limited research opportunities, mistrust, fear of mistreatment, safety and confidentiality, competing priorities and HIV stigma. Facilitators to HIV research participation were peer involvement and engagement, monetary and non-monetary incentives, flexibility and choices, multiple modalities and methods, and transcenteredness. Conclusion: It is critical to address the social and economic vulnerabilities surrounding HIV research participation for TW. Results from this study can inform the design and implementation of gender-affirming and culturally tailored approaches to HIV research with TW.